2011
DOI: 10.1111/j.1600-0854.2011.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sorting Motifs of AtβFruct4 for Trafficking from the ER to the Vacuole Through the Golgi and PVC

Abstract: Although much is known about the molecular mechanisms involved in transporting soluble proteins to the central vacuole, the mechanisms governing the trafficking of membrane proteins remain largely unknown. In this study, we investigated the mechanism involved in targeting the membrane protein, AtβFructosidase 4 (AtβFruct4), to the central vacuole in protoplasts. AtβFruct4 as a green fluorescent protein (GFP) fusion protein was transported as a membrane protein during transit from the endoplasmic reticulum (ER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…To identify trafficking pathways involving AP1M2, we examined the effect of the ap1m2-1 mutation on various post-Golgi trafficking pathways. Soluble cargo proteins sporamin and Arabidopsis aleurain-like protease (AALP) and the membrane cargo protein AtβFructosidase4 were used as GFP-fusion proteins to analyze vacuolar trafficking in ap1m2-1 protoplasts (36,37). Unlike the situation in WT, these proteins were not processed in the ap1m2-1 mutant, as seen by the increase in intensity of the precursor band, and this defect was suppressed in protoplasts from ap1m2-1 plants expressing AP1M2:myc (Fig.…”
Section: Ap1m2 and Ap1m1 Biochemically Interact With Endogenous γ-Adamentioning
confidence: 99%
“…To identify trafficking pathways involving AP1M2, we examined the effect of the ap1m2-1 mutation on various post-Golgi trafficking pathways. Soluble cargo proteins sporamin and Arabidopsis aleurain-like protease (AALP) and the membrane cargo protein AtβFructosidase4 were used as GFP-fusion proteins to analyze vacuolar trafficking in ap1m2-1 protoplasts (36,37). Unlike the situation in WT, these proteins were not processed in the ap1m2-1 mutant, as seen by the increase in intensity of the precursor band, and this defect was suppressed in protoplasts from ap1m2-1 plants expressing AP1M2:myc (Fig.…”
Section: Ap1m2 and Ap1m1 Biochemically Interact With Endogenous γ-Adamentioning
confidence: 99%
“…After synthesis at the ER membrane, cargo membrane proteins are incorporated into coat protein complex II (COPII) vesicles [52] upon interaction between coat proteins and ER export signals before delivery to the Golgi [53, 54]. Various export signals have been described in yeast, mammals and plants, including diacidic (D/E-X-D/E), dihydrophobic (ISI), diaromatic motifs (FF, YY and FY) [35, 37, 38, 51, 55, 56] and the motif PI [36]. Impaired or altered recognition of export signals due to mutations or masking by fusion moieties may result in partial or total retention of the protein within the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains elusive if the roles of TMD length in targeting would be applied to multiple spanning membrane proteins. The demonstration of various sorting signals in multiple TMD proteins such as SCAMP1 further indicated the complexity of the targeting mechanism of proteins with multiple TMDs in plant cells (Cai et al, 2011;Jung et al, 2011).…”
Section: The N Terminus Of Vit1 Contains Both a Putative Er Export Simentioning
confidence: 99%
“…The C terminus of tonoplast two-pore K+ channels has been proved to contain targeting information for different types of vacuoles both in rice (Oryza sativa) and Arabidopsis thaliana (Isayenkov et al, 2011;Maîtrejean et al, 2011). Another study with Arabidopsis b-Fructosidase 4 has identified EEE and LCPYTRL sequence motifs as sorting signals on the way from the TGN to the central vacuole (Jung et al, 2011). Similar to cases in mammalian cells and yeast, a conserved dileucine motif is also involved in the targeting of tonoplast membrane proteins in plant cells, as recorded for several proteins like the monosaccharide transporter ERD SIX-LIKE1 (ESL1), the molybdate transporter2 (MOT2), two pore channel1 (TPC1), peptide transporter1 (PTR1), and inositol transporter1 (INT1) (Yamada et al, 2010;Gasber et al, 2011;Komarova et al, 2012;Larisch et al, 2012;Wolfenstetter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%